Contestation and Harmonization of Islamic Legal Istinbath: A Study of the Ahlu Hadith and Ahlu Ra’yi Schools - Mardhiya Agustina; Ahmad Farid Atqiya; Muhammad Sholah Ulayya (Ad-dawl : Jurnal Islamic Studies, 2026)
This study aims to examine the definition, background of emergence, and characteristics of the thought of Ahlu Hadith and Ahlu Ra’yi in the development of Islamic law. In addition, this study also aims to analyze the factors that cause differences in the methods of legal istinbath between the two groups. The method used is qualitative research with a library research type, sourced from classical books, works on Islamic legal thought, and relevant scientific literature. The approaches used include a historical approach to trace the development of the two schools and a normative approach to analyze the methods of legal determination employed. The results of the study show that the emergence of Ahlu Hadith and Ahlu Ra’yi was influenced by different social, political, and geographical conditions, particularly between the regions of Hijaz and Iraq. Ahlu Hadith tends to prioritize a textual approach by strongly adhering to the Qur’an, hadith, and the athar of the Companions, while limiting the use of reason. Meanwhile, Ahlu Ra’yi develops a more rational approach through ijtihad, qiyas, and considerations of public interest in responding to issues not explicitly found in the texts. These differences are not contradictory but rather represent methodological variations in understanding Islamic law. Therefore, both approaches have significant contributions to the dynamics and development of Islamic law up to the present time.